KAJIAN FUNGSI INTERMEDIASI PERBANKAN INDONESIA MASA KRISIS EKONOMI TAHUN 1997-1998 - arianto, bisma (Fakultas Ekonomi Universitas PGRI Adi Buana, 2014)
Monetary and banking crises happened in Indonesia in 1997 has brought a very fundamental change in Indonesia economy. These crisis, which then become an economic crisis, has put Indonesian banking into a big difficulty. When the economic crisis happened on July 1997, the Indonesian banking's level of Loan to Deposit Ratio (LDR) tended to decrease. This Fact showed that the implementation of Indonesian banking's intermediation function was decreasing. Moreover, the occurring issues of excess reserve which was not allocated for credit matters, and the increasing of fund placement through Sertificate of Bank Indonesia (SBI) volume, has caused a decrease and ever a failure in the implementation of Indonesian banking's intermediation function. It's very important to observe the decreasing of Indonesian banking's intermediation function because it can directly affect the development of real sector and then it will have an impact on the development of Indonesian economy. The intermediation function of national banking has already worked, but the yearly increase is relatively slow. The increasing of national banking's excess reserve since 1997 shows that the banking's operational in distributing the loan to real sector is not optimal. Which the increasing position of Sertificate of bank Indonesia (SBI) on banking shows that banking tends to allocate their funds to get short term profit and it also has small risk level than allocating the fund for loan. Indonesian banking's intermediation function has actually worked well, but what happen then is that the increasing of banking's credit level can not matched with the increasing of Third Party Fund (DPK) level. The effort of banking in increasing Loan to Deposit Ratio (LDR) by distributing into that loan can not be done by the banking itself. Other party support, especially from government in establishing a condusive situation also can attract the development of business.